2019
DOI: 10.1111/apps.12188
|View full text |Cite
|
Sign up to set email alerts
|

“What a Match!”: The Specific Role of Resources in the Relation Between Demands and Vigour in Elite Sport

Abstract: The triple‐match principle, as outlined by the Demand‐Induced Strain Compensation (DISC) Model, states that resources are most effective when they match particular demands. The present study investigates the role of match in elite sport with regard to the relation between sport‐related demands, sport‐related resources, and vigour (i.e., physical strength, cognitive liveliness, and emotional energy). We hypothesised that moderating effects of resources on the relation between demands and vigour are most likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…, ). Furthermore, the studies in this special issue show that the availability of (matching) job resources may help employees offset the negative implications of job demands (i.e., buffering effect; Balk et al, ) or fire up employees to use their job resources to make the most of a demanding situation (i.e., boosting effect; Balk et al, ; Madrid & Patterson, ). Finally, this set of studies also indicate that some environmental circumstances such as leadership support or national culture may alleviate or intensify the effects of job resources (Molina & O’Shea, ; Rattrie et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, ). Furthermore, the studies in this special issue show that the availability of (matching) job resources may help employees offset the negative implications of job demands (i.e., buffering effect; Balk et al, ) or fire up employees to use their job resources to make the most of a demanding situation (i.e., boosting effect; Balk et al, ; Madrid & Patterson, ). Finally, this set of studies also indicate that some environmental circumstances such as leadership support or national culture may alleviate or intensify the effects of job resources (Molina & O’Shea, ; Rattrie et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Building on the assumptions of the DISC‐model, Balk, De Jonge, Oerlemans, and Geurts () provide a theoretical explanation for when and why job resources may have a stronger positive effect than usual. Examining a sample of semi‐professional and professional sportsmen in the Netherlands who are paid to engage in their sports, these authors found support for the triple match principle: high emotional resources buffered the detrimental effect of high emotional resources on emotional energy (i.e., buffering effect), while the combination of high physical job resources and job demands resulted in increased physical strength (i.e., activity enhancing effect).…”
Section: Introductionmentioning
confidence: 99%
“…For example, situational awareness and fatigue management may be valuable for employees to achieve their objectives safely (e.g., by helping them to identify possible risky situations) as well as to recover adequately from psycho-physical fatigue, respectively. However, by not being directly aimed at taking actions to manage the risk of infection at work (i.e., there is no match between job demand and job resource) [ 119 , 120 ], the aforementioned resources might not be useful for workers to effectively reduce the psychological and physiological costs associated with the perceived risk. Conversely, job resources that are more specifically directed at risk management may be more valuable for workers to actively cope with the perceived risk of infection (i.e., job resource match job demands) [ 119 ], thus reducing the associated costs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, interactional stressors faced by employees can adversely affect their behavior in an organization (Brotheridge and Grandey, 2002;Naseer et al, 2018). Stressful events in organizations have been proven to prevent employees from performing well in organizations (De Clercq et al, 2019), due to excessive cognitive, emotional and sometimes, physical demands exerted on individuals (Balk et al, 2020). However, only few study considered the organizational mistreatment factors on employee performance, such as workplace ostracism and bullying at workplace (Baranik et al, 2017;Robert, 2018;De Clercq et al, 2019;Shen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%